The nature of the expansion of the Authority of The State Administrative Court regarding Government Administration Law - Rizal Haliman; Sadjijono; Slamet Suhartono; Hufron (Technium Social Sciences Journal, 2021)
This research is a normative juridical research. The nature of the expansion of the authority of the State Administrative Court as a result of the establishment of Law No. 30 of 2014 which expands the meaning of State Administrative Decrees and adds material for Government Administration Actions, causing an expansion of the authority of the State Administrative Court to receive, examine and adjudicate in resolving disputes over Government Actions which were previously not explicitly regulated in Law No. 51 of 2009.